Universal Sikhism: An Aid to Moral Upliftment - ., K.T.K (Journal of Dharma, 1980)
Dalip Singh, Universal Sikhism: An Aid to Moral Upliftment; Yoga and Sikh Teachings: New Delhi: Bahri Publications' Pvt. Ltd.